Spatiotemporal dispersal study of mangrove Avicennia marina and Rhizophora apiculata propagules - Wong, Yun Yun; Foong, Swee Yeok; Wang, Youshao; Dai, Lu; Mao, Limi; Goh, Thian Lai (Penerbit Universiti Kebangsaan Malaysia, 2022)
The propagule dispersal pattern of the two common mangrove species, Avicennia marina (Forsk.) Vierh. and Rhizophora apiculata Blume at a mangrove fringed coast, in the southwest tip of Penang Island was examined. Propagule dispersal study of both species were carried out by release and recapture method, while early developments of propagule were observed by an on-site tethering system. A. marina propagules recorded higher dispersal rate as compared to R. apiculata. After 60 tidal cycles, almost all propagules had moved away from the initial release site under the influence of strong wave current. The A. marina propagules were observed to grow better and faster than the R. apiculata propagules. However, the propagules of both species eventually failed to establish at the study site due to strong wave effect as well as unfavourable soil condition. A. marina and R. apiculata were found to adopt different strategies in propagule dispersal and early growth. A. marina was notably better adapted to thrive in the coastal environment. In a similar open coastal area, wave current and soil condition are suggested to be the most critical factors affecting the mangrove propagule dispersal and early establishment.